BREAKING THE ADDICTION TO TECHNOLOGY ADOPTION. (April 2014) - Bryan, Stirling; Mitton, Craig; Donaldson, Cam
ABSTRACT A major driver of cost growth in health care is the rapid increase in the utilisation of existing technology and not simply the adoption of new technology. Health economists and their health technology assessment colleagues have become obsessed by technology adoption questions and have largely ignored 'technology management' questions. Technology management would include the life‐cycle assessment of technologies in use, to assess their real‐world performance; and monitoring of technology indication creep. A rebalancing of focus might serve to encourage a more self‐critical and learning culture amongst those involved in technology evaluation analysis. Further, health economists and health technology assessment analysts could make a more significant contribution to system efficiency through rebalancing their efforts away from technology adoption questions towards technology management issues. Copyright © 2014 John Wiley & Sons, Ltd.